COMMUNITY-BASED TOURISM RESILIENCE IN PERINGGASELA VILLAGE, EAST LOMBOK REGENCY - Danu Satria Prayuda; Mawar Junita; I Wayan Bratayasa (International Journal of Multidisciplinary Reseach, 2026)
Tourism development increasingly faces various challenges, including environmental changes, economic uncertainty, natural disasters, and socio-cultural transformations that affect destination sustainability. Community-based tourism has emerged as an important approach for strengthening destination resilience through active local participation and utilization of local resources. This study aims to analyze community-based tourism resilience in Peringgasela Village, East Lombok Regency, using the perspective of Social–Ecological Resilience Theory. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving village government representatives, tourism awareness groups, weaving communities, local business actors, and local residents. Data were analyzed using the interactive model of data reduction, data presentation, and conclusion drawing. The findings indicate that tourism resilience in Peringgasela Village is built through four interconnected dimensions: social resilience, economic resilience, cultural resilience, and institutional resilience. Strong social capital, community participation, local economic diversification, preservation of traditional weaving culture, and stakeholder collaboration contribute significantly to strengthening the destination's adaptive capacity. The study concludes that strengthening community participation and local resources can create a resilient and sustainable tourism system at the village level.